Dielectrics of graphene oxide decorated with nanocomposite silica-coated calcium copper titanate (CCTO) nanoparticles - Bharatiya D.; Kumar S.; Raghunandan S.; Paik P. (My University, 2025)
This work presents the synthesis of the noble nanocomposites of silica-coated calcium copper titanate–graphene (CCTO@SiO 2 –GO) by the established sol–gel method. This paper showed the decoration of CCTO@SiO 2 NPs on the surface of graphene oxide and how the decoration/attachment depends on various environmental and instrumental factors like sonication time, stirring rate, centrifugation rpm and the thickness of silica shell coated on CCTO NPs. The prepared CCTO@SiO 2 –GO composites were characterized by suitable characterization techniques. FESEM and TEM confirmed the morphological study of nanocomposites and how the CCTO@SiO 2 NPs are attached to the surface of GO sheet. FTIR has shown the presence of O–H, N–C groups which help in the formation of types of bonds between CCTO@SiO 2 NPs and GO. This work further revealed an excellent result of a dielectric study, indicating that the best-decorated CCTO@SiO 2 NPs over the surface of the GO sheet cause the increment of dielectric constant ε′ from 10 2 up to 10 5 . Meanwhile, this study also suggested high loss ε″ up to 10 6 at a lower frequency, i.e. 20 Hz at RT which can be useful for microelectronic devices. This variance of dielectrics is due to the effect of polarization and decoration of CCTO@SiO 2 NPs over the GO sheets. As the frequency increases from 20 Hz to 2 MHz, the dielectric constant ε′, as well as the loss of ε″, reached up to 10 2 values for the highest decorated material. Our study also clearly explained a uniform variation in dielectric constant ranges from 1 × 10 2 to 1.5 × 10 4 at a different temperature range from room temperature to 560 °C with a frequency range of 3 × 10 4 Hz to 2 × 10 6 Hz, and the value varies accordingly with the synthesis method. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.